Joint scheduling method of peak shaving and frequency regulation using hybrid energy storage considering degeneration characteristic - Yubo Wang; Xingang Zhao; Yujing Huang (IET Renewable Power Generation)
Abstract In this paper, a joint scheduling method of peak shaving and frequency regulation using hybrid energy storage system considering degeneration characteristic is proposed. Firstly, incorporating degradation costs of the hybrid energy storage system with respect to the depth of discharge and cycle lifetime, long‐term costs of battery energy storage and flywheel energy storage are modelled and transformed to short‐term costs related to real‐time operation. Then, a joint scheduling model is proposed for hybrid energy storage system to perform peak shaving and frequency regulation services to coordinate and optimize the output strategies of battery energy storage and flywheel energy storage, and minimize the total operation cost of microgrid. In addition, three optimal dispatching strategies for hybrid energy storage system to participate in the auxiliary service of power grid are proposed based on the established auxiliary service model. Simulation studies demonstrate that the proposed joint scheduling method can optimize the power of different energy storage, alleviate the degradation process of battery energy storage. Compared with the scenario without scheduling hybrid energy storage system, scheduling hybrid energy storage system can reduce the total operation cost, and the electricity cost of microgrid is reduced by 13.13%.